Strategies for modifying drug residence time and ocular bioavailability to decrease treatment frequency for back of the eye diseases. (2nd January 2019) - Shatz, Whitney; Aaronson, Jeffrey; Yohe, Stefan; Kelley, Robert F.; Kalia, Yogeshvar N.
ABSTRACT: Introduction : Treating posterior eye diseases has become a major area of focus for pharmaceutical and biotechnology companies. Current standard of care for treating posterior eye diseases relies on administration via intravitreal injection. Although effective, this is not without complications and there is great incentive to develop longer-acting therapeutics and/or sustained release delivery systems. Here, we present an overview of emerging technologies for delivery of biologics to the back of the eye. Areas covered : Posterior eye diseases, intravitreal injection, age-related macular degeneration, anti-VEGF, ocular pharmacokinetics, novel technologies to extend half-life, in vivo models, translation to the clinic, and hurdles to effective patient care. Expert opinion : Posterior eye diseases are a worldwide public health issue. Although anti-VEGF molecules represent a major advance for treating diseases involving choroidal neovascularization, frequent injection can be burdensome for patients and clinicians. There is a need for effective and patient-friendly treatments for posterior eye diseases. Many technologies that enable long-acting delivery to the back of the eye are being evaluated. However, successful development of novel therapies and delivery technologies is hampered by a multitude of factors, including patient education, translatability of in vitro / in vivo preclinical data to the clinic, and regulatory challenges associated with novel technologies.